Development of an automatic tool for dose management in digital mammography (Brazilian Journal of Radiation Sciences, 2019)
INTRODUCTION: Digital mammography units usually record the entrance surface exposure (ESE) and the average glandular dose (AGD) received by the patient for each exposure. This information is usually available in the DICOM headers and can be used to perform dose surveys. The main objective of this paper was to develop a software tool to automatically analyze digital mammography image headers in order to assess the dose received by each patient. MATERIALS AND METHODS: Images were acquired on a Senographe Essential (GE Healthcare) digital mammography system, using automatic exposure control. Patients with breast implants were excluded. Images were queried and downloaded from the institution's PACS using the DCM4CHE 3.0 open source toolkit. MATLAB code was developed to extract the breast thickness and the AGD from the DICOM headers. This data was exported to a spreadsheet for further analysis. RESULTS: Demographic data, breast thickness and dose per view for 59 patients were analyzed. A AGD of 1.56 mGy and 1.53 mGy was obtained for the craniocaudal (CC)  and mediolateral oblique (MLO) views respectively. CONCLUSIONS: the developed tool proved to be useful for the dosimetric survey of digital mammographic techniques, allowing us to implement a dose management program.